Pengaruh Inovasi Terhadap Kinerja Bisnis Pada UMKM Kerajinan Sulaman, Bordir dan Pertenunan Di Sumatera Barat - Primadona primadona (Politeknik Negeri Padang, 2019)
This study aims to determine the effect of innovation on business performance in Micro, Small and Medium Enterprises (SMEs) Embroidery and Weaving in West Sumatra. This study uses a quantitative method with regression data analysis using SPSS to determine the effect of the two variables. The research location was West Sumatra with 205 respondents spread across 6 regions, namely Bukittinggi City, Pariaman City, Tanah Datar District, Padang City, Sawahlunto City and Payakumbuh City. The results of the study reveal that innovation has an influence on business performance in embroidery and embroidery craft SMEs in West Sumatra. The contribution of innovation in influencing business performance is 74, 7 percent while the rest is influenced by other factors not found in this study. The limitation of this study is that the method used is quantitative and for further research to be carried out with mixed methods between the two to be able to produce more in-depth conclusions. Furthermore, it is also suggested to be able to add several variables in looking at business performance in SMEs, especially SMEs, embroidery and weaving in West Sumatra.